Native language interference: The interference of passive voice - Saptin Dwi Setyo Hastuti; Pratomo Widodo (EduLite: Journal of English Education, Literature and Culture, 2020)
This study investigated the interference of Bahasa Indonesia passive voice norm on English sentence. There are many studies that investigated the interference of native language on the learning of target language. Most of the studies talked about interference in the level of lexical, grammatical, phonetic, syntactical, and many more. However, the study about interference of a norm have never been discussed before. Thus, it is important to conduct this study to give some prove that norm of languages may interfere language learning. This study involved 50 students of Tour and Travel Business Department at Sekolah Tinggi Pariwisata (STP) AMPTA Yogyakarta. The data was collected by giving students 3 sentences in Bahasa Indonesia and they had to write them in English. The sentences that the students had produced were compared to the correct one. The finding shows that most of the students’ sentences were interfered by the norm of passive voice in Bahasa Indonesia. It is due to the lack of students’ understanding toward the concept of passive voice norms in both of Bahasa Indonesia and English. Thus, the teacher must give clear explanation about the norm of passive voice in both of languages.